CIVIL JUSTICE IN SOUTH AFRICA - D. Van Loggerenberg (BRICS Law Journal)
The South African adversarial system of civil procedure in the High Court owes its origin to that of England. As with all civil procedural systems, the South African system is not stagnant. Its primary sources, namely Acts of Parliament and rules of court, are constantly amended in an attempt to meet the changing needs of society. Court delay and costinefficient procedural mechanisms, however, contribute to public dismay. The High Court, in the exercise of its inherent power to regulate its process, do so with the purpose of enhancing access to justice. The advantage of the system lies in the fact that it is not cast in stone but could, subject to the Constitution of the Republic of South Africa, 1996, be developed to make it more accessible to the public whilst protecting the public’s fundamental rights entrenched in the Constitution and, in this regard, particularly the right to afair trial embedded in sec. 34 of the Constitution. This contribution gives an overview of the system with reference to the court structure, the judiciary, the process in the High Court and its underlying principles, appeals, class actions and alternative civil dispute resolution mechanisms.